Effects of applying the instructional systems design process on transfer of training to workplace - Malekzadeh, Robabeh (2014)
The ultimate purpose of training transfer is to improve individual and organisational performance. It is a huge waste of organizational resources, if training cannot be transferred into the workplace. Therefore, measuring transfer of training achievement is essential to ensure that employees apply what they have learned from training context on their job. Numerous researches have studied the issues of training transfer in the past decades, however, training transfer literature shows that because of lack of a standard and widely accepted methodology, measuring transfer of training still is a complicated component. Therefore, this study, aims to explore the effects of application of the ISD process (in terms of the ADDIE model) on transfer of training in order to define a systematic instructional procedure that could address a sound method for measuring transfer of training at the workplace. This study involved 51 “Administrative Assistants” and their immediate supervisors working at all divisions of the Ministry of Science, Technology and Innovation (MOSTI) in Malaysia. The study is a Type 2 developmental research that utilized a quasi-experimental design (posttest only nonequivalent control group design) to determine the difference in the transfer of training achievement. Two groups of employees were trained on the effective communication skills at workplace. The experimental group received a structured training program using the ISD process in terms of ADDIE model (Analyze, Design, Develop, Implement, and Evaluate) through the researcher while the control group received the conventional training by the training department. The two groups were assessed using a self-assessment checklist containing a five-point behavioural observation itemized rating scale, five months after the period of training. Also, the immediate supervisors of these groups assessed them in the same way and period. The findings of this study indicate that transfer of training was affected by using the ISD process. Although, the assessment of the trainees by their immediate supervisors did not report the different scores of training transfer achievement for them, the results showed that there is a significant difference between the experimental and control groups on training transfer achievement and the experimental group had better transfer of training achievement than the control group. The study contributes to the HRD research and practice by empirically investigation of the effects of applying the ISD process on transfer of training and provides the HRD researchers and practitioners with a sound instructional procedure for measuring transfer of training which is a key indicator of training effectiveness.